Temporomandibular bozukluğu olan bireylerde orofasiyal manuel terapiye core stabilizasyon eğitiminin eklenmesi : bir randomize kontrollü çalışma - İğrek, Sultan (My University, 2024)
Amaç: Çalışmanın amacı, orofasiyal manuel terapiye (OMT) eklenen core stabilizasyon eğitiminin (CSE) sonuç ölçümlerini iyileştireceği hipotezi ile Temporomandibular bozukluğu (TMB) olan hastalarda üç farklı tedavinin etkinliğini karşılaştırmaktır. Yöntemler: Yaşları 18-60 arasında olan, TMB-redüksiyonlu disk deplasmanlı 45 hasta randomizasyon kullanılarak üç gruba ayrıldı: kontrol grubu (n=15) hasta eğitimi ve evde egzersiz aldı; ayrıca OMT grubuna (n=15) orofasiyal manuel terapi uygulandı; CSE grubu (n=15) ise OMT ve CSE programını aldı. OMT ve CSE hafta boyunca haftada bir kez uygulandı. Tedavi sonrasında hastalar yeniden değerlendirildi. Ağrı, tetik nokta (TN) duyarlılığı, Temporomandibular Eklem (TME) hareket açıklığı (EHA), fonksiyonelliği, yüz asimetrisi, pelvik tilt ve lumbal lordoz açısı, esneklik, stabilize edici kasların performansı ve uyku kalitesi sırasıyla numerik ağrı skalası, dijital algometre, cetvel, Helkimo İndeksi, mezura, Palpation Meter, Bubble inklinometre, el parmak zemin mesafesi ve otur - uzan testleri, basınç biofeedback ünitesi ve Pittsburgh Uyku Kalite İndeksi kullanılarak değerlendirildi. Bulgular: Tüm gruplarda ağrı, TN duyarlılığı, TME EHA, çene fonksiyonu ve uyku kalitesinde iyileşmeler gözlense de en etkili iyileşme CSE grubunda gözlendi. CSE ile pelvik tilt ve lordoz açısı, lumbal bölge ve hamstring esnekliği iyileştikçe çene fonksiyonu, yüz asimetrisi, TN'lerin duyarlılığı ve TME EHA'nın iyileştiği bulunmuştur. Tartışma: TMB olan hastalarda egzersiz ve orofasiyal manuel terapiye eklenen core stabilizasyon egzersizlerinin semptomlarını iyileştirmede üstünlük sağladığı belirlenmiştir.

Objective: This study was designed to compare the effectiveness of three different treatments in patients with Temporomandibular disorder (TMD) with the hypothesis that core stabilization training (CST) added to orofacial manual therapy (OMT) would improve outcome measures. Methods: Fourty-five patients aged 18–60 years with TMD-reduction disc displacement were separated into three groups using randomization program: the control group(n=15) received patient education and a home-based exercise program; additionally, to the OMT group (n=15) received orofacial manual therapy; and the CST group (n=15) received the CST program. OMT and CST were applied in one sessions per week for 10 weeks. The patients were reevaluated after treatment. Pain, trigger point (TP) sensitivity, Temporomandibular Joint (TMJ) range of motion (ROM), functionality, facial asymmetry, pelvic tilt, and lumbar lordosis angle, flexibility, performance of stabilizing muscles, and sleep quality were evaluated by using Numeric Pain Scale, digital algometer, ruler, Helkimo Index, tape, Palpation Meter, bubble inclinometer, finger to floor distance and sit and reach tests, pressure biofeedback unit, and Pittsburgh Sleep Quality Index, respectively. Results: The improvements in pain, TP sensitivity, TMJ ROM, jaw function, and sleep quality were observed in the three groups, however the most effective improvement was observed in the CST group. It has been found that as pelvic inclination and lordosis angle, and lumbar region and hamstring flexibility improve with CST, jaw function, facial asymmetry, sensitivity of TPs, and TMJ ROM also improve. Discussion: It was determined that core stabilization exercises added to exercise and orofacial manual therapy were superior in improving symptoms in patients with TMD.
Adding core stabilization training to orofacial manual therapy in ındividuals with temporomandibular disorders : a randomized controlled study
Keywords: ağrı; core stability; core stabilizasyon; egzersiz; exercise; Fizyoterapi; manuel terapi; manuel therapies; pain; Physiotherapy; Temporomandibular bozukluk; Temporomandibular disorder